Friday
March 24, 2017

Post a New Question

Posted by on Saturday, December 3, 2011 at 10:12am.

f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7)

Find: (fog)(x)
(gof)(x)
(fog)(-1)

  • Composite Functions - , Saturday, December 3, 2011 at 5:58pm

    f(g) = (7g+28)/(g-3)
    = (7(3x+28)/(x-7) + 28)/(3x+28)/(x-7) - 3)
    = x

    g(f) = (3f+28)/(f-7)
    = (3(7x+28)/(x-3) + 28) / ((7x+28)/(x-3) - 7)
    = x

    How odd! However, if you solve for f-1(x) you get g(x) and vice-versa.

    f(g(-1)) = f(-1) = -1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question